Biology - Chia, Lok Thye; R.S Jacqueline; Nalini B. (Ace Ahead STPM Text, 2019)
This books is specially written for Sixth Form students taking Biology Paper 2 in the current STPM assessment system. It contaisn all the stipulated in the STPM Biology syllabus for Second Term.